The Challenges of Savings on Credit Unions in Creating Wealth: A Case Study of Zambia Army Savings and Credit Union - Ian, Mwila; Richard, Engr. Dr Kasongo Mwale (International Journal of Finance, 2020)
Purpose: The aim of this study was to identify the challenges of savings on Zambia Army Savings and Credit Unions in creating wealth and recommend possible solutions. Methodology: The study used mixed research methods to collect qualitative and quantitative data, as both could not give the satisfactory results due to weaknesses in each method. Eighty (80) respondents were sampled of which seventy were sampled from members of ZASCU in survey questionnaire and the other ten (10) were for in-depth interview from management. Top management of six (6) respondents and four (4) respondents from operation level were purposively sampled for expert sampling and in-depth interviews were used as a data collection technique. The other respondents were randomly sampled selected using probabilistic sampling, where every individual had an equal chance of being selected. Quantitative data was analyzed using SPSS version 21 and qualitative data was analyzed using thematic content analysis and document review. The research study's results collected through the questionnaire, in-depth interviews and document review showed that ZASCU had challenges of savings in creating wealth. Findings: The results showed the following challenges: 26% of participants cited delay in disbursing of money, 14% respondents identified inadequate online system and 19% was for lack of skilled personnel. Members had another concerned of limitation in loan facility as 21% of the respondents cited it and 20% had a concern for underutilization of funds at ZASCU. ZASCU needs to be as strategic in the market as it faces stiff competition from other lending institutions providing similar services. Unique contribution to theory, policy and practice: The study recommended that ZASCU needed to have modern technologies for online system, skilled personnel, prudence in financial management, paying on time and increase on loan disbursements. The challenges of savings are affecting negatively on ZASCU in creating wealth and this has caused loss of confidence by stakeholders, and the sooner the solutions to mitigate the saving challenges are found and implemented the better.